Zmiany zasobów produkcji gospodarstw indywidualnych objętych kontraktacją w latach 2001-2004 - Dzieża, Grzegorz (The Changes of Production Resources of Individual Farms Contracted Between 2001 and 2004, 2005)
The competitiveness of individual farms on the farm product market forces changes of elementary production resources. In the farms of 50 ha area which cooperate with the food processing plant, an increase of farm area and changes of machinery and other equipment was noticed. The investment most often concerned tractors, expensive machinery for carrying and harvesting and also elements of infrastructure such as storages and water-butts. Big area farms specialized in vegetable production displace and smaller ones in co-operation with food processing plants.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 192-196